Guidance for evidence-informed policies about health systems: assessing how much confidence to place in the research evidence. - Simon Lewin (Public Library of Science (PLoS), 2012)
In the third paper in a three-part series on health systems guidance, Simon Lewin and colleagues explore the challenge of assessing how much confidence to place in evidence on health systems interventions.